2016
DOI: 10.1002/pat.3986
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(2-hydroxyethyl methacrylate)-based molecularly imprinted polymer nanoparticles containing timolol maleate: morphological, thermal, and drug release along with cell biocompatibility studies

Abstract: a This work was aimed to synthesize and characterize poly(2-hydroxyethyl methacrylate) [poly (HEMA)]-based molecularly imprinted polymer nanoparticles (MIP NPs) containing timolol maleate (TM) via precipitation polymerization. The molecular structures of the MIP and non-imprinted polymer (NIP) NPs were compared by means of Fourier transform infrared spectroscopy. The morphological observations by using scanning electron microscopy and transmission electron microscopy confirmed the formation of MIP NPs as small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In general, the potential of polymer matrices (MIP and NIP) for the detection and absorption of drug is influenced by various factors such as pH, monomer to drug ratio, type of absorption medium, and drug concentration, etc. According to the results of the previous study, the absorption of drug in acidic and non‐acidic environments was not clear very well, but at pH 7.4, there was the greatest difference between MIP and NIP samples, because the concentration of OH − and H + was low, and the drug and monomer were in the best condition for the formation of a bond. In the acidic pH, both the drug and the monomer were protonated, and the monomer was ionized and degraded in the basic pH; consequently, there was no possibility of effective hydrogen bonding between the monomer and the drug.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, the potential of polymer matrices (MIP and NIP) for the detection and absorption of drug is influenced by various factors such as pH, monomer to drug ratio, type of absorption medium, and drug concentration, etc. According to the results of the previous study, the absorption of drug in acidic and non‐acidic environments was not clear very well, but at pH 7.4, there was the greatest difference between MIP and NIP samples, because the concentration of OH − and H + was low, and the drug and monomer were in the best condition for the formation of a bond. In the acidic pH, both the drug and the monomer were protonated, and the monomer was ionized and degraded in the basic pH; consequently, there was no possibility of effective hydrogen bonding between the monomer and the drug.…”
Section: Resultsmentioning
confidence: 90%
“…In recent years, researchers have clearly shown that nanoscale medical devices are capable of performing very complex tasks, ie, enhanced drug delivery within biological tissues owing to their unique properties . Many studies have been conducted to synthesize and develop nanomaterials used for advanced drug delivery systems, especially hydrophobic medicines which cannot be prescribed without a controlled dose program . In this regard, the application of polymer materials is strongly recommended due to their versatility, suitable physical chemistry characteristics, and ability to conjugate with drug molecules as well as acceptable rate of degradation under appropriate biological conditions, preserving the concentration of drugs in their therapeutic window …”
Section: Introductionmentioning
confidence: 99%
“…The serum‐free culture medium without sample was chosen as a control group. Cell viability was calculated by the following equation: Cell viability(%)=true(Abs sampleAbs controltrue)×100 …”
Section: Methodsmentioning
confidence: 99%
“…[192] Abbasy et al recently demonstrated that MIPs can exhibit high selectivity for proteins compared to nonimprinted polymers. [193] Moreover, studies have repeatedly demonstrated their stability across different stresses and biocompatibility, [194][195][196] whilst demonstrating enhanced retention of analytes. Their potential is further boosted by the low cost and facile preparation methods needed to achieve the high selectivity.…”
Section: Molecular Imprinted Polymersmentioning
confidence: 99%